2021
DOI: 10.3389/fimmu.2021.686439
|View full text |Cite
|
Sign up to set email alerts
|

Precision Engineering of an Anti-HLA-A2 Chimeric Antigen Receptor in Regulatory T Cells for Transplant Immune Tolerance

Abstract: Infusion of regulatory T cells (Tregs) engineered with a chimeric antigen receptor (CAR) targeting donor-derived human leukocyte antigen (HLA) is a promising strategy to promote transplant tolerance. Here, we describe an anti-HLA-A2 CAR (A2-CAR) generated by grafting the complementarity-determining regions (CDRs) of a human monoclonal anti-HLA-A2 antibody into the framework regions of the Herceptin 4D5 single-chain variable fragment and fusing it with a CD28-ζ signaling domain. The CDR-grafted A2-CAR maintaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 59 publications
(76 reference statements)
4
40
0
Order By: Relevance
“…Bioluminescence imaging demonstrated preferential migration of HLA-A2 CAR Tregs towards the HLA-A2+ skin allograft (64), indicating that HLA-specific CAR Tregs can migrate towards the location where regulation is required. Muller et al demonstrated similar effects where HLA-A2-CAR Tregs migrate to the HLA-A2+ transgenic islets in a model of induced diabetes in immunodeficient mice (68). In addition, Noyan et al studied a different HLA-A2 CAR, in a model where immunodeficient NOD rag gamma (NRG) mice were transplanted with human HLA-A2+ skin grafts (26).…”
Section: Migration Of Car Tregs Towards Allograftsmentioning
confidence: 97%
See 4 more Smart Citations
“…Bioluminescence imaging demonstrated preferential migration of HLA-A2 CAR Tregs towards the HLA-A2+ skin allograft (64), indicating that HLA-specific CAR Tregs can migrate towards the location where regulation is required. Muller et al demonstrated similar effects where HLA-A2-CAR Tregs migrate to the HLA-A2+ transgenic islets in a model of induced diabetes in immunodeficient mice (68). In addition, Noyan et al studied a different HLA-A2 CAR, in a model where immunodeficient NOD rag gamma (NRG) mice were transplanted with human HLA-A2+ skin grafts (26).…”
Section: Migration Of Car Tregs Towards Allograftsmentioning
confidence: 97%
“…MacDonald et al demonstrated a very low proportion of induced cell death in HLA-A2-positive cells when co-cultured with high ratios of CAR Tregs, but similar experiments with the presence of HLA-A2-positive PBMCs show that cytolytic activity was negligible (62). Another study in the setting of murine allogeneic islet transplantation indicated that despite the accumulation of CAR Tregs in allografts, no islet destruction could be observed, which suggested that CAR Tregs are not cytotoxic to allogeneic islets (68). Since these studies have described Treg stability directly after generation and infusion, long-term stability still remains to be investigated in order to establish safety.…”
Section: Phenotypic Stability Of Car Tregsmentioning
confidence: 98%
See 3 more Smart Citations